Pengujian Aplikasi Beberapa Jenis Bahan Aktif Bakterisida terhadap Serangan Bakteri Xanthomonas sp. pada bibit Eucalyptus pellita - Kusumaningsih, Kartirahayu; Putra, Hansen Tanaka (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2024)
One of the problems in cultivating Eucalyptus pellita seedlings in Industrial Plantation Forest (HTI) nurseries is the attack of Xanthomonas sp bacteria. Seedlings that are attacked by this bacteria will experience spots on the leaves, wilt, fall off, and ultimately cause the death of the seedlings. Controlling bacterial attacks by using bactericides is one effort to minimize bacterial attacks. The purpose of this research is to determine the effect of the type of bactericidal active components, namely Oxitetracycline, Zinc Thiazole, and Copper Oxside, and the spraying time interval on the growth of Xanthomonas sp on NA (Nutrient Agar) media, reducing the incidence and severity of bacterial attacks on E. pellita seedlings. The research used 2 treatments factor, namely kinds of bactericidal active component and spraying time interval. Test of bactericidal active component was carried out on laboratory (in-vitro) and direct testing on sedlings. The research results showed that bactericides with the active components Oxitetracycline, Zinc Thiazole and Copper Oxcide, were able to inhibit the growth of Xanthomonas sp on NA media. Oxitetracycline resulted in a higher reduction in the incidence and severity of Xanthomonas sp attacks on E pellita seedlings compared to other active ingredients, namely 61.36% for a reduction in incidence and 36.25% for a reduction in severity. The bactericide spraying time interval of 1 and 2 weeks did not have a significant effect on reducing the incidence and severity of Xanthomonas sp attacks on E. pellita seedlings.